The Three Levels Hierarchy of Commercial Processes of Industrial Enterprises - Elena SHKARUPETA; Diana SAVON; Andrey SAFRONOV; Galina KRUZHKOVA; Dina BORISOVA (Communications of International Proceedings, 2021)
The article presents a system process model of industrial enterprise, classified management decisions from a position of functions and elements of the enterprise activity with the objective of developing an adequate strategy for the management of commercial activities. Based on the proposed hierarchical model algorithm is developed for determine the integral management efficiency of industrial enterprise. The model of product portfolio management is proposed as the basis for finding the characteristics and evaluation of consumer behavior. As a management tool has developed a methodology for identifying the properties of the products relevant to the consumer.
Keywords: System Model; Management Strategy; Integrated Performance Management Indicator; The Structure Of The Product Portfolio; Strategy; Consumer Behavior